Development of lawns in response to applications of imazapic alone or combined with imazapyr1 - Marques, Ricardo F. [UNESP] (2021)
Successive mowings are the major maintenance cost of lawns. These costs have led to the search for alternatives to mechanical management. This study aimed to determine the effects of imazapic herbicide doses applied alone or combined with imazapyr as a growth regulator of Tifton 419 and Zoysia grasses. The experimental design was randomized blocks with four replicates, and the treatments consisted of four doses of herbicide imazapic applied alone (35; 70; 105 and 140 g a.i. ha-1) and three doses of imazapic + imazapyr mixture (7.875 + 2.625; 15.57 + 5.25 and 23.625 + 7.875 g a.i. ha-1) in two sequential applications on both grass lawns. Visible injury symptoms, canopy height, height and number of inflorescences, and total dry matter of clippings were determined. Applications of imazapic alone or combined with imazapyr effectively reduced all morphological variables of Tifton 419 grass. Imazapic applied alone or mixed with imazapyr provided adequate control of growth and quantity of dry matter of Zoysia grass clippings. Still, with some application doses of this herbicide, the number of inflorescences present in the lawns increased.